Extended Holstein Polaron Mass - Yavidov, B.Ya. (Відділення фізики і астрономії НАН України, 2010)
The renormalization of the effective mass of an electron due to the small polaron formation is studied within an extended Holstein model. It is assumed that an electron moves along a onedimensional chain of ions and interacts with ions vibrations of the neighboring chain via a long-range density-displacement type force. By means of exact calculations, the renormalized mass of a nonadiabatic small polaron is obtained in the strong coupling limit. The obtained results are compared with analogous ones within the ordinary Holstein model. The effect of the polarization of vibrations of ions on the small polaron mass is discussed. Вивчено перенормування маси електрона в результатi утворення малого полярону в межах розширеної моделi Холстейна. Передбачається, що електрон рухається по одномiрному ланцюжку iонiв i взаємодiє з коливаннями iонiв сусiднього ланцюжка внаслiдок далекодiйних сил. Шляхом прямих обчислень отримано перенормовану масу недiабатичного малого полярону в межах сильного зв’язку. Отриманi результати порiвняно з аналiтичними результатами Холстейна. Обговорено вплив коливань iонiв з рiзними поляризацiями на масу малого полярону.